Determinan Perilaku Tes IVA di Puskesmas Sawangan Kota Depok Tahun 2022 - Dewi, Indah Rahma; Hadiwiardjo, Yanti Harjono; Saleh, Arman Yurisaldi; Purwaningastuti, Diana Agustini (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2023)
Background. WHO in 2020 states that the fourth most common cancer is cervical cancer and GLOBOCAN in 2018 states that it is the second most common cancer in Indonesia. VIA is one of the programs for cervical cancer early detection implemented in Indonesia, however the coverage relatively low. Aim. Identification determinant of VIA behavior among 30-50 years old women in Puskesmas Sawangan, Depok. Method. Analytical observational study with a cross-sectional design. The sample was women aged 30-50 years at Puskesmas Sawangan. The data collected with consecutive sampling technique. The research instrument is a questionnaire. Data analysis used are Chi-square and logistic regression. Result. Majority of respondents were unemployed, multiparous, had good knowledge, negative attitudes, poor information access, did not have family support, and had not been tested for VIA. There is a significant relationship between parity (p-value = 0.005) and information access (p-value = 0.001) with VIA behavior and no significant relationship between knowledge, attitude, work and family support with VIA behavior (p-value > 0.05). Multivariate tests showed that parity was the dominant factor associated with VIA behavior (OR =9.106). Conclusion. Parity and information access are related to VIA behavior, while knowledge, attitudes, employment, and family support are not related to VIA behavior.